Gender disparity in hepatobiliary endoscopy training and delivery: Results of a nationwide survey - Kotha, Sreelakshmi; Long, Matthew; Berry, Philip (Endoscopy International Open, 2025)
There are far fewer female, independent endoscopic retrograde cholangiopancreatography (ERCP) practitioners than men in the UK. This study aimed to explore what lies behind the disparity by examining the current state of training, attitudes, and other factors that may influence trainees’ decision to pursue ERCP training, with a view to identifying modifiable factors.Anonymized responses to an electronic survey distributed to gastroenterology trainees and independent ERCP practitioners in the UK were collected and analyzed.Of 214 respondents 45% were female. Whereas gender distribution in non-hepatobiliary therapeutic endoscopy was balanced, only 29% of ERCP trainees were female. Eighty percent of those who worked less than full time (LTFT) were female, but 32% felt that LTFT was incompatible with ERCP training. Concerningly, one-quarter of female respondents reported that they had been discouraged. It was noted that females are often treated differently within endoscopy units, including by patients. Fifty percent of females indicated that radiation exposure affected their decision to train in ERCP, compared with 22% of males. A question specific to trainers revealed that 95% felt that male gender was associated with increased confidence. In free-text responses, valuable insights into trainees’ personal experiences were provided, and a selection is presented. Finally, strategies to redress the gender imbalance are proposed.Gender disparity in HPB endoscopy exists and is stark. Underlying this are attitudes, assumptions, and environmental factors that will require systemic and sustained correction. Ideas about how to address this challenge need to be explored.
Keywords: Pancreatobiliary (ERCP); Quality and logistical aspects; Training; Quality management